2007
DOI: 10.1038/sj.ejhg.5201944
|View full text |Cite
|
Sign up to set email alerts
|

X inactivation in triploidy and trisomy: the search for autosomal transfactors that choose the active X

Abstract: Only one X chromosome functions in diploid human cells irrespective of the sex of the individual and the number of X chromosomes. Yet, as we show, more than one X is active in the majority of human triploid cells. Therefore, we suggest that (i) the active X is chosen by repression of its XIST locus, (ii) the repressor is encoded by an autosome and is dosage sensitive, and (iii) the extra dose of this key repressor enables the expression of more than one X in triploid cells. Because autosomal trisomies might he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 71 publications
1
27
0
Order By: Relevance
“…XaXaXi or XaXiXi), has led to models for XCI 'count' that involve dosage of autosomal factors. Such a singular locus has not been identiWed by the study of autosomal trisomies, although there remain some autosomal segments that have not been identiWed in a trisomic region (Migeon et al 2008). …”
Section: X-chromosome Aneuploidies and Aneusomies: Control Of X-linkementioning
confidence: 99%
“…XaXaXi or XaXiXi), has led to models for XCI 'count' that involve dosage of autosomal factors. Such a singular locus has not been identiWed by the study of autosomal trisomies, although there remain some autosomal segments that have not been identiWed in a trisomic region (Migeon et al 2008). …”
Section: X-chromosome Aneuploidies and Aneusomies: Control Of X-linkementioning
confidence: 99%
“…It has been shown, however, that more than one X chromosome is active in the majority of human triploid cells [20] . It has been suggested that the active X is selected by repression of its XIST locus: a dosage-sensitive repressor is encoded by an autosome, and the extra dose of this key repressor enables the expression of more than one X in triploid cells [20] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, however, that more than one X chromosome is active in the majority of human triploid cells [20] . It has been suggested that the active X is selected by repression of its XIST locus: a dosage-sensitive repressor is encoded by an autosome, and the extra dose of this key repressor enables the expression of more than one X in triploid cells [20] . Since females with 47,XXX carry a normal set of diploid autosomes, it could be hypothesized that rare copy number variants in an autosomal repressor cause an increased expression of this repressor which results in more than one X chromosome being activated.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, XIST has all the hallmarks of a housekeeping gene, ubiquitously expressed, with a 5 0 CpG island; it is expressed, from all X chromosomes in the zygote of either sex, albeit at low levels, until the time in embryogenesis when the locus on the future active X is turned off, and methylated in both males and females. In addition, the study of 69, XXX and 69, XXY triploid cells provides compelling evidence that it is the active X, rather than the inactive X that is chosen (Migeon et al 2008) (Fig. 2).…”
Section: Choice Of Active X Rather Than Inactive Xmentioning
confidence: 97%
“…2). Despite the equal dose of X-linked Rnf12, one X is inactive in 47, XXY diploid cells, whereas, in 69 XXY cells, neither X may be inactivated (Migeon et al 2008).…”
Section: Role For Other Non-coding Rnas Within the Xic May Be Speciesmentioning
confidence: 98%